From Tryptophan to Auxins: Investigating their roles in the biology of the plant growth-promoting bacterium Pantoea agglomerans 33.1. - Figueredo, Everthon Fernandes (2024)
The biosynthesis of indole-3-acetic acid (IAA) tryptophan-dependent by plant growth-promoting bacteria (PGPB), plays a fundamental role in promoting growth in plants, and is also related to cell signaling and bacterial functional metabolism. Tryptophan amino acid serves as the primary precursor for IAA synthesis by bacteria. It is suggested that the trp genes, along with endogenous tryptophan synthesis, act as regulators of the synthesis of this auxin, particularly in the IPyA pathway mediated by the ipdC gene. Alterations in tryptophan and IAA homeostasis and synthesis can influence numerous interdependent metabolic processes, including those related to plant growth promotion traits in bacteria. The PGPB Pantoea agglomerans 33.1 is a known sugarcane and others crop growth promoter, revealing genes associated with IAA biosynthesis in the IPyA pathway and tryptophan synthesis in its genome. Therefore, the present study aimed to investigate the role of trp genes and endogenous tryptophan synthesis in regulating IAA biosynthesis and to analyze the effects of both molecules on the metabolism and biology of PGPB Pantoea agglomerans 33.1. The influence of tryptophan synthesis genes (trpE and trpB), and the ipdC gene on the regulation of the IAA synthesis, was evaluated by obtaining strains with gene silencing via CRISPR interference (CRISPRi), a variant of the CRISPR-Cas9 system used for specific control of gene transcription without altering the target DNA sequence. Four strains were generated, three of them with single silencing of trpE, trpB, and ipdC genes, and one strain with double silencing of trpE and trpB. Gene repression by CRISPRi showed significant impacts on bacterial growth, gene expression, and synthesis of indolic compounds and IAA. The identification and quantification of these compounds showed direct relationships among trpE, trpB, and ipdC genes, highlighting an intricate network of genetic and metabolic regulation in P. agglomerans 33.1. Additionally, the impacts of CRISPRi-mediated gene silencing on plant growth promotion traits and in the metabolism of P. agglomerans 33.1 were investigated, revealing variable alterations depending on the silenced gene and endogenous tryptophan and IAA synthesis showing effects on bacterial morphology and physiology, as well as impacts on IAA biosynthesis and degradation, biofilm formation, carotenoid production and in the bacterial fitness. Finally, it was demonstrated through metabolomic analysis that silencing of trp and ipdC genes significantly alters bacterial metabolism with implications for bioactive compound synthesis patterns affecting plant-microorganism interaction. The findings of this study enhance the understanding of tryptophan, IAA, and other indolic compound synthesis by P. agglomerans 33.1, paving the way for future studies of bacteria-plant interaction and plant growth promotion, enabling the optimization of this strain as a bioinoculant agent through targeted manipulation of its metabolism